Factors Affecting Income of Smallholder Goat Farmers in Vyas Municipality, Tanahun (Sudurpaschim Spectrum, 2026)
Goat farming is an integral part of rural livelihoods, which is common for smallholder farmers of Nepal. Despite being a lucrative sector, especially for the rural farming households, commercialization of goat farming is very less indicating some sort of hindrances. A research was conducted in Ranigaun village of Vyas municipality-11, Tanahun from February to July 2024 to understand the income and its determinants. Data was collected from 86 households through KoboCollect mobile application using semi-structured questionnaires. Data analysis was done by STATA. The results pointed out that the average yearly income from goat farming was NRs. 60,469.76 per household. Multiple regression analysis revealed that years of schooling and goat farming experience have statistically significant positive relationship with smallholder goat farmers’ income at 1% significance level. Group membership is positively significant (5% significance level). Absenteeism at households, having one or more members migrated to abroad, has negatively significant (p < 0.01) impact on income. Major problems in goat production were reported to be inadequate knowledge on balanced feeding (index value of 0.77) and insufficient funds for scaling-up to commercial level (0.71). Since association with some sort of groups are found to have positive impact, it is recommended that formation of such groups should be the priority of development workers. Farmers’ group should also prioritize their activities to enhance the capacity of their members by providing practical skills like goat feed management. Besides, such groups can be a platform for learning-sharing on their personal experiences.